THE ANALYSIS OF TECHNOLOGICAL PROCESS OF EXPEDITIONARY MAINTENANCE OF MOTOR TRANSPORT - Naumov, V. S. (Science and Transport Progress, 2009)
The basic technological operations of the automobile freight forwarding process have been determined. The base algorithms of the freight forwarding technological process have been proposed. The fundamental flow charts of technological process in use have been formalized and analyzed.